School responsiveness to quality rankings: An empirical analysis of secondary education in the Netherlands - Pierre Koning; Karen van der Wiel (Institute for the Study of Labor (IZA), 2010)
This paper analyzes the response of secondary schools to changes in their quality ratings. The current analysis is the first to address the impact of quality scores that have been published by a newspaper (Trouw), rather than public interventions. Our research design exploits the substantial lags in the registration and publication of the Trouw scores and that takes into account all possible outcomes of the ratings, instead of the lowest category only. Overall, we find evidence that school quality performance does respond to Trouw quality scores. Both average grades increase and the number of diplomas go up after receiving a negative score. For schools that receive the most negative ranking, the short-term effects (one year after a change in the ranking of schools) of quality transparency on final exam grades equal 10% to 30% of a standard deviation compared to the average of this variable. The estimated long run impacts are roughly equal to the short-term effects that are measured.
Keywords: H75; I20; D83; 330; School quality; school accountability; Allgemeinbildende Schule; Dienstleistungsqualität; Bewertung; Wirkungsanalyse; Bildungsniveau; Niederlande